(untitled) (CIPEEX, 2025)
Introduction: Swimming is a complex sport that depends on several factors for good performance in the aquatic environment. Body composition analysis is essential in sports to check the health and performance of athletes. Training aims to promote adaptations and optimal performance in major competitions. Therefore, the objective of this study was to analyze the body composition of high-performance swimmers using bioimpedance. Methodology: Twenty-nine swimmers were selected to participate in the study. Bioimpedance was applied before training, and after the training period, we analyzed whether there were significant changes in body composition. Partial results: The data obtained through bioimpedance before training provide information on lean and muscle mass, weight, height, and basal metabolic rate (BMR), cellular health, fat, hydration, and intra- and extracellular water. Final considerations: At the moment, training is being carried out with the athletes, and it will later be verified whether it was beneficial for the swimmers.